Cracking the code: Understanding lecturer performance and student success - Tri Kuncoro; Marji Marji; Mazarina Devi; Aji Prasetya Wibawa; Ming F. Teng (International Journal of Education and Learning, 2022)
One of the essential factors in a learning process, especially in higher education, is lecturer performance. This study aims to discover the impact of a lecturer's performance on students learning outcomes in the online learning environment. Lecturer performance is represented by four aspects which are the lecturer's performance on learning technology (X1), the lecturer's performance on learning pedagogy (X2), the lecturer's performance on supporting learners (X3), and the lecturer's performance on supporting educators (X4). This quantitative research approach aims to discover one variable's cause-and-effect relationship to another. The subject of this study is 37 lecturers and 146 students. The result shows that the lecturer's performance contributes 43.1% to students' learning outcomes. It is known that learning technology and pedagogy aspects have a significant effect on students' learning outcomes. However, supporting learners and educators does not significantly impact students' learning outcomes. Therefore, the lecturer's performance positively impacts learning outcomes and is valuable for further online learning development. A potential research contribution could be to investigate further the relationship between specific aspects of a lecturer's performance and students' learning outcomes in an online learning environment. this study's findings have significant implications for higher education institutions seeking to improve online learning experiences for students. By identifying the specific aspects of lecturer performance that most impact learning outcomes, institutions can provide targeted support and training to their lecturers, ultimately leading to improved learning outcomes for students in online learning environments.